Aphasia and topic initiation in conversation: a case study. Issue 1 (19th October 2012) - Barnes, Scott E.; Candlin, Christopher N.; Ferguson, Alison
Abstract Background Aphasiologists often research, assess and treat linguistic impairment and its consequences for daily life separately. Studies that link the language used by people with aphasia to routine communicative activities may expand the linguistic forms treated as relevant for successful communication by people with aphasia. Previous research has suggested that initiating topics in conversation can be problematic for people with aphasia, but it has not been widely investigated. Aims This paper uses Conversation Analysis to examine how a person with aphasia initiated topics in everyday conversation. It describes the utility of and‐prefacing for topic initiation. Methods & Procedures A person with chronic aphasia ('Valerie') was recruited to participate and was video‐recorded speaking with four conversation partners. Approximately 3.5 h of recordings were collected, and transcribed according to conversation analytic conventions. Topic initiations in this data set were identified and analysed using conversation analytic procedures. Outcomes & Results It was found that topic initiations often led to trouble, and that Valerie recurrently used and‐prefaced turns when initiating topics (e.g. and how was your turkey?). This paper argues that and‐prefacing was an advantageous method for initiating topics because it smoothed the conversational discontinuities that this action creates. Conclusions & Implications These findings are consistent with previous observations about the hazardousness of topic initiation for people with aphasia. Valerie's use of and‐prefacing suggests that conjunctions and other turn prefaces may be useful for promoting successful communication by people with aphasia during everyday conversation. Future investigation should identify if and how other people with aphasia use turn prefacing when initiating topics, and whether this changes over time.